Keping Puzzle Yang Hilang: Menelaah Hak Yang Sirna Terhadap Narapidana - Azis, Muhammad Abdul; Putri, Riski Ananda Kusuma; Rahman, Nur (Jurnal Hukum & Pembangunan, 2022)
Prisons have a reputation for being cages of deprivation of freedom and atonement for wrongdoing. Prisoners lose their independence because prisons restrict their movement, including their sexual needs, which is like the "missing piece of the puzzle." The discussion in this article tries to explore the missing piece of prisoners' rights, examine, and analyze the impact of the Conjugal Visit program for prisoners in Indonesia, to bring new light to the realization of human rights in the prison system aimed at legal protection and fulfillment of human rights. This article uses normative legal methods. Systematic legal comparison is used to examine literature study data. The result is that, sexual rights are fundamental. Prisoners must be fulfilled. Unmet basic needs can harm physical and mental health. The principle of basic human needs. Law of the Republic of Indonesia Number 36 of 2009 concerning Health supports Conjugal Visit in Indonesia. Legal system theory and international practice in the implementation of Conjugal Visit should be a reference for implementation in Indonesia.